2003
DOI: 10.1097/00129492-200301000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Type III Tympanoplasty applying the Palisade Cartilage Technique: A Study of 61 Cases

Abstract: The palisade cartilage technique is suitable to manage difficult pathologic conditions in middle ear surgery. It was demonstrated that the palisade cartilage technique can be combined safely with titanium ossicular replacement prostheses. Regarding postoperative hearing results, the negative preselection of pathologic conditions must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 12 publications
1
34
1
Order By: Relevance
“…Shield-sliced tragal cartilage-perichondrium 97.67% Air bone gap < 30 dB Sismanis et al [14] Revision cartilage tympanoplasty 93.5% Air bone gap < 30 dB Neuman et al [5] Cartilage palisade 100% Air bone gap < 30 dB H.Chopra et al [9] Temporalis fascia with anterior tucking 95% Air bone gap < 30 dB Dornhoffer et al [8] Cartilage palisade 100% Air bone gap < 20 dB Ioanis Adonis et al [10] Cartilage graft 98.4% Air bone gap < 20 dB K.Desarda et al [11] Cartilage graft 96% Air bone gap < 20 dB Our study Cartilage-perichondrium composite graft 96.36% Air bone gap <30 dB…”
Section: Graft Used Take Up In % Hearing Results Khan Et Al [13]mentioning
confidence: 99%
See 2 more Smart Citations
“…Shield-sliced tragal cartilage-perichondrium 97.67% Air bone gap < 30 dB Sismanis et al [14] Revision cartilage tympanoplasty 93.5% Air bone gap < 30 dB Neuman et al [5] Cartilage palisade 100% Air bone gap < 30 dB H.Chopra et al [9] Temporalis fascia with anterior tucking 95% Air bone gap < 30 dB Dornhoffer et al [8] Cartilage palisade 100% Air bone gap < 20 dB Ioanis Adonis et al [10] Cartilage graft 98.4% Air bone gap < 20 dB K.Desarda et al [11] Cartilage graft 96% Air bone gap < 20 dB Our study Cartilage-perichondrium composite graft 96.36% Air bone gap <30 dB…”
Section: Graft Used Take Up In % Hearing Results Khan Et Al [13]mentioning
confidence: 99%
“…Neumann et al reported a graft take rate of 100% in their palisade cartilage tympanoplasty study, and they did not observe resorption or recurrent defects of the rebuilt tympanic membrane. 5 Khan et al used a shield-sliced tragal cartilage-perichondrium composite graft, and their success rate was 97.67%. 13 Sismanis et al reported their revision tympanoplasty cases, and their success rate was 93.5%.…”
Section: Graft Used Take Up In % Hearing Results Khan Et Al [13]mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuman et al [11] reported post operative recurrence in 1.6 % cases with no facial weakness and otorrhea.…”
Section: Postoperative Complicationsmentioning
confidence: 98%
“…The thought of a prospective study using cartilage as to reconstruct the tympanic membrane came after going through the limited number of clinical studies exploring the outcomes of cartilage palisade in tympanoplasty procedures. [8][9][10][11][12] The aim of this article was to compare the graft acceptance rates and auditory outcomes of cartilage tympanoplasty operations using the palisade technique with those of primary tympanoplasty using temporalis fascia in two groups of patients.…”
Section: Introductionmentioning
confidence: 99%